Postscript on 'Treasury' Shares. - Paton, W. A. (The Accounting Review, 1969)
Abstract Acquisitions by corporations of their own outstanding shares are one of those transactions which seem to be peculiarly subject to misunderstanding. From time to time efforts have been made to shed light on the nature of such transactions, but to date the gloom of confused thinking and questionable policy has not been fully dispelled in this special segment of corporate finance. About a half-century ago the author of this article published an article which he naively assumed would settle the basic issue, once and for all, and in other writings since this piece appeared he has tried his hand at the chore of promoting straight thinking on the subject of "treasury" shares. These comments represent a sort of postscript to the earlier attempts, and they are drafted with the thought that a continuing campaign is necessary to keep the leaven of logic alive wherever there is persistent susceptibility to error. The first step in grappling with the subject of "treasury" shares is to recognize that such shares have substantially the same status as stock that has never been issued. This essential point, unfortunately, has usually been overlooked in the textbooks and other writings on accounting and finance.